Avaliação dos parâmetros do processo de anodização na formação de nanotubos de TIO2 e suas implicações na morfologia e na adesão ao substrato de titânio - Renz, Renata Pedrolli (2015)
This study evaluates the electrochemical anodization process parameters in the formation of titanium nanotubes on titanium sheets in order to determine their implications on the morphology of the tubes and the film/substrate adhesion. The evaluated parameters were the anodization time, applied potential, water content in the electrolyte and the electrolyte stirring (ultrasound bath and magnetic agitation) in an ethylene glycol electrolyte with addition of ammonium fluoride. The obtained results were compared to those obtained from the anodization in an aqueous acid electrolyte (mixed solution of hydrofluoric and phosphoric acid). Analyzes using scanning and transmission electron microscopy were performed for the morphological characterization of the samples. Rutherford backscattering spectrometry was used to determine the composition and density profile of the different oxide layers formed. Tensile tests (pull out) were used in order to determine the adhesion of the titanium nanotubes to the substrate. The results showed that it is possible to form titanium nanotubes with various morphologies by changing the parameters of the electrolytic process. The average adhesive tension of nanotubes ranged from 2,82 ± 0,27 Mpa to 5,18 ± 3,61 MPa, however, it was not possible to observe a direct relationship between the morphologies formed and the obtained adhesive tension values.